Trinuclear complexes of palladium(ii) with chalcogenated N-heterocyclic carbenes: catalysis of selective nitrile–primary amide interconversion and Sonogashira coupling. Issue 38 (22nd September 2017) - Dubey, Pooja; Gupta, Sonu; Singh, Ajai K.
Abstract : The interconversion of nitriles to amides and Sonogashira coupling were catalyzed with Pd(ii ) complexes (0.5–2 mol%). Abstract : 3-Methyl-1-(2-(phenylthio/ seleno)ethyl)-1 H -benzo[ d ]imidazol-3-ium iodide (L1 /L2 ), a precursor of sulfated/selenated N-heterocyclic carbene, was synthesized by the reaction of benzimidazole with 1, 2-dichloroethane followed by treatment with PhS/SeNa and MeI. The reaction ofL1 /L2 with Ag2 O followed by treatment with [Pd(CH3 CN)2 Cl2 ] (metal to ligand ratio 3 : 2), i.e. transmetallation, resulted in trinuclear palladium(ii ) complexes [Pd3 (L1 /L2 -HI)2 (CH3 CN)Cl6 ] (1–2 ). The complexes were characterized with 1 H, 13 C{ 1 H} and 77 Se{ 1 H} NMR (2 only), elemental analyses, HR-MS and single-crystal X-ray diffraction. The geometry of three Pd atoms in each complex is nearly square planar. The Pd–S/Se, Pd–C, Pd–N and Pd–Cl bond distances (Å) in1 /2 are 2.3179(19)/2.4312(10), 1.968(7)/1.952(4), 2.073(8)/2.079(4) and 2.2784(19)–2.298(2)/2.292(2)–2.3003(15), respectively. In both the complexes, all Cl are trans to each other. For the central Pd atom, two benzimidazole rings are also trans to each other. The C–H⋯Cl non-covalent interactions result in a three-dimensional network. The moisture and air insensitive trinuclear Pd(ii ) complexes1 and2 are thermally stable and efficient as a catalyst for nitrile–amide interconversion and amine-free Sonogashira C–C coupling (in the presence of CuI). The optimum temperature is 80 °C for the interconversion and 110 °C for the coupling. The catalytic protocols are applicable to both aliphatic and aromatic amides/nitriles. The optimum catalyst loading is 1 mol% for the C–C coupling and 0.5 to 1 mol% for the interconversion. K2 CO3 as a base gives the best result for Sonogashira C–C coupling. In the conversion of nitriles to amides, the formation of an acid was not detected. After using once, 1 /2 can carry out the conversion of ten fresh lots of nitriles to amides with almost the same efficiency. The real catalytic species for the interconversion and coupling appear to be based on Pd(ii ) and Pd(0), respectively.